2003
DOI: 10.1002/yea.992
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between G+C content, ORF‐length and mRNA concentration in Saccharomyces cerevisiae

Abstract: RNA biogenesis is a tightly-regulated process. The levels and timing of expression of a gene depends on its particular function. However, gene expression levels may also depend on structural features. Here we describe the analysis of gene expression of 4977 ORFs using DNA microarrays covering the whole genome of three different S. cerevisiae strains, wild-type and tho2 and thp1 mutants with a general effect on mRNA biogenesis. We show that transcripts from G+C-rich ORFs accumulate at higher concentrations than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 42 publications
7
31
1
1
Order By: Relevance
“…A transcription initiation enhancer element (Cavener and Ray, 1991) was introduced 5# of the initiation codon. GC content was adjusted from 47% in the 5# coding region to 33% (Marín et al, 2003), and rare yeast codons were replaced. Using eight partially overlapping long-mer oligonucleotides, the optimized 561-bp 5# region of PsCYP720B4 was synthesized by PCR and ligated to 891 bp of the native 3# region.…”
Section: Expression Of Diterpene Synthases and Pscyp720b4 In Yeastmentioning
confidence: 99%
“…A transcription initiation enhancer element (Cavener and Ray, 1991) was introduced 5# of the initiation codon. GC content was adjusted from 47% in the 5# coding region to 33% (Marín et al, 2003), and rare yeast codons were replaced. Using eight partially overlapping long-mer oligonucleotides, the optimized 561-bp 5# region of PsCYP720B4 was synthesized by PCR and ligated to 891 bp of the native 3# region.…”
Section: Expression Of Diterpene Synthases and Pscyp720b4 In Yeastmentioning
confidence: 99%
“…Interestingly, top Rrm3-bound genes were more expressed in npl3D cells, suggesting that replication obstacles occur preferentially at the highest transcribed genes in the absence of Npl3 (Fig. 7B), these genes preferentially being shorter all over the genome (Marin et al 2003). In this sense, although gene ontology analysis revealed that genes involved in ribosome biogenesis or intron-containing genes were significantly overrepresented in npl3D cells, this is consistent with the fact that ribosome biogenesis genes are highly transcribed and represent the major class of intron-containing genes in yeast.…”
Section: Genome-wide Dna Replication Impairment In Npl3d Cells Detectmentioning
confidence: 99%
“…Another possibility is that regions of high GC content are associated with a chromatin modification that facilitates recombination (43). Relevant to this point is the observation that there is a very significant positive correlation between GC content of genes and their mRNA levels (40).…”
Section: Vol 26 2006 Global Analysis Of Yeast Meiotic Recombinationmentioning
confidence: 99%